CATÁLOGO DE LOS CLÉRIDOS DE CHILE (COLEOPTERA: CLERIDAE) - Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
A catalog of the chilean Cleridae is made. Six subfamilies, 18 genera and 58 species are recognized. Taxonomic data of genera and taxonomic, distributional, ecological and biological data of species are provided. After the revisión of types, the following new synonyms are established: - Thanasimus gayi Spinola, 1849 = Eurymetopum ebumeocinctum (Spinola), 1849. - Falsopelonium Pie, 1950c = Corinthiscus Fairmaire y Germain, 1861. - Falsopelonium impressipenne Pie, 1950c = Corinthiscus insignicomis Fairmaire y Germain, 1861.